Răspuns :
Explicație pas cu pas:
[tex] \frac{3a + 2b}{6} = \frac{3b + c}{7} = \frac{a + 4c}{11} = k[/tex]
a, b, c sunt prime adică pot fi 1,3,5,7
Răspuns:
[tex]\frac{3a+2b}{6} =\frac{3b+c}{7} =\frac{a+4c}{11} =k[/tex]
3a+2b=6k
3b+c=7k
a+4c=11k
3a+2b=6k
2b si 6k sunt nr. pare ⇒ 3a=nr. par ⇒ a=2 (singurul nr. prim par)
3·2+2b=6k ⇒ b=3k-3
3b+c=7k ⇒c=7k-3(3k-3) ⇒ c=7k-9k+9, c=9-2k
a+4c=11k ⇒4c=11k-2 ⇒[tex]c=\frac{11k-2}{4}[/tex]
[tex]9-2k=\frac{11k-2}{4}[/tex] /·4
36-8k=11k-2 ⇒ 19k=38 ⇒ k=2
b=3·2-3 ⇒ b=3
c=(11·2-2):4 ⇒ c=20:4 ⇒ c=5
[tex]\frac{3x2+2x3}{6} =\frac{3x3+5}{7} =\frac{2+4x5}{11}[/tex]
[tex]\frac{12}{6} =\frac{14}{7} =\frac{22}{11} =2[/tex]
Explicație pas cu pas: